Financial Literacy, Risk Perception, and Investment Preferences: A Study on Millennials in Jakarta - Wisnu Putra, Aziz; Eurelia Wayan, Maria (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2023)
The investment trend in Indonesia has increased with the presence of investors categorized as the millennial generation. The determination of investment instruments selected is influenced by the level of financial literacy and risk perception of the investors. This study aims to analyze how financial literacy and risk perception affect investment preferences amongst the millennials. Using the millennials in the five municipalities of Jakarta as a case in point, this study contributes to providing analytical data and an overview of the level of financial literacy and risk perception as well as the investment preferences of the millennial generation. The findings of this study serve as material for investors to consider in making investments and offer information or insights to existing and new investors. Financial literacy is comprised of financial knowledge, financial behavior, and financial attitude as stated by Rooij, Lusardi, and Alessie. Risk perception is measured by risk propensity and risk aversion. Investment preferences in this study are regarded as investment instruments prioritized and preferred by the millennials, namely stocks, mutual funds, bonds, gold, deposits, foreign currencies, property, and peer-to-peer lending. This study employed a quantitative approach and collected data through questionnaires. The data obtained from a total of 148 respondents were processed using descriptive statistical analysis by SPSS. The findings of this study indicate that the millennials in the five municipalities of Jakarta have a high level of financial literacy and risk perception. The most preferred investment instrument is stock investment. The majority of the millennial generation in Jakarta owns mutual funds, gold, and equities, and most began investing when they were 20 years old. The 20- to 29-year-old age group in the five municipalities of Jakarta choose to invest in equities, while the 30- to 39-year-old age group in gold.